Quality characteristics and volatile compounds of foam mat dried corn flour - Teoh, Li Shing; Lasekan, Ola; Azeez, Shakirah (Wiley-Blackwell Publishing, 2016)
Foam mat drying is good in dehydrating liquid foods in a short time. The porous structure of foam material contributes to high drying rate and consequently shorter dehydration time. Corn flour was produced using foam mat drying and its quality was compared to freeze-dried corn flour. Different concentrations of egg albumen (10, 15 and 20%) and whipping time (5, 10 and 15 min) were used. Foaming characteristics of corn slurry produced were investigated. Corn slurry produced with 20% egg albumen and 15 min whipping time was chosen and the slurry was dried at different temperatures (60, 70 and 80C). Their physicochemical properties and volatile compounds were determined. Foam mat dried corn flour at 60C was found to be the overall optimum corn flour with the highest nutritional composition (protein, 21.51%; crude fat, 4.16%; and crude fiber, 7.52%). However, freeze-dried corn flour gave better color appearance and more volatile compounds.